A Systematic Review of Autologous Fat Grafting in the Treatment of Acute and Chronic Cutaneous Wounds. Issue 5 (May 2020) - Malik, Dean; Luck, Joshua; Smith, Oliver J.; Mosahebi, Afshin
Abstract : Background: There is a growing interest in the regenerative potential of autologous fat. Adipose-derived stem cells, within the stromal vascular fraction of lipoaspirate samples, demonstrate anti-inflammatory, immunomodulatory, and angiogenic properties. This systematic review aimed to determine the efficacy and safety of autologous fat therapies for wound healing, with an evaluation of the quality of evidence provided by the literature. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we searched Ovid Medline, Embase, and Cochrane Library databases from inception to November 2018. We included all human studies where wounds were treated with lipotransfer, cell-assisted lipotransfer, stromal vascular fraction products, or isolated adipose-derived stem cells. Study screening and data extraction were performed by 2 authors. The quality of evidence was evaluated using the GRADE approach. Results: The search strategy returned 5027 citations. From these, 10 observational case series were included in the qualitative synthesis; there were no randomized controlled trials. Patient characteristics, wound etiology, and intervention type differed markedly between studies, precluding formal meta-analysis. Autologous fat grafting was associated with satisfactory wound healing in all studies with low complication rates. However, the quality of evidence was consistently very low. Conclusions: Autologous fat grafting is an emerging therapeutic option for challenging wounds, although there is insufficient evidence to conclusively demonstrate its effectiveness and adverse event profile. Based on the literature to date, it is unclear whether one type of autologous fat therapy is superior. Well-designed, blinded, prospective randomized controlled trials with adequate methodologic details and objective outcome measure reporting are essential. PROSPERO ID: CRD42017081499.